Effectiveness of Learning Electric Power System Transmission using Higher Other Thinking Skill based Simulation - Agus Junaidi; Rahmaniar Rahmaniar (AL-ISHLAH: Jurnal Pendidikan, 2022)
The research discusses the effectiveness of learning in the field of Electrical Power Transmission (EPT). The model developed by applying the Higher Other Thinking Skill (HOTS) strategy using computer simulation media at levels 4 and 5, which is not yet optimal in improving learning outcomes in the EPT field. The HOTS strategy at the level of analysis and evaluation is needed in the study of electric power transmission which has abstract study material through complex mathematical modeling, so it requires HOTS. Measurement of the effectiveness of EPT learning begins with a needs analysis, through 14 questions identifying learning needs. Furthermore, building EPT simulation media equipped with HOTS Practice questions, and Construct Model-Tracking-Simulation and Analysis (CTA) syntax in learning, as a strategy for achieving EPT learning. The media has been validated by 4 experts with the Aiken's V approach through media instrument validation with a value of 0.86 which is declared valid. It has been tested the effectiveness of learning as measured through trials in the experimental class and control class on 22 students in the control class and 23 students in the experiment class (45 respondents). In the control class, an inquiry model is applied, while the experimental class is a CTA based simulation model. From the results of the tests that have been carried out, the average value of the experimental class was 78,53 and 68,57 in the control class. The application of the simulation-based HOTS thinking skills strategy is effectively used by students in EPT learning.